Does Labor Legislation Benefit Workers? Well-Being after an Hours Reduction - Daniel S. Hamermesh; Daiji Kawaguchi; Jungmin Lee (Institute for the Study of Labor (IZA), 2014)
Are workers in modern economies working too hard – would they be better off if an equilibrium with fewer work hours were achieved? We examine changes in life satisfaction of Japanese and Koreans over a period when hours of work were cut exogenously because employers suddenly faced an overtime penalty that had become effective with fewer weekly hours per worker. Using repeated cross sections we show that life satisfaction in both countries may have increased relatively among those workers most likely to have been affected by the legislation. The same finding is produced using Korean longitudinal data. In a household model estimated over the Korean cross-section data we find some weak evidence that a reduction in the husband's work hours increased his wife's well-being. Overall these results are consistent with the claim that legislated reductions in work hours can increase workers' happiness.
Keywords: J22; J23; J28; 330; happiness; overtime work; rat-race